1994
DOI: 10.1149/1.2055015
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemically Deposited Diffusion Barriers

Abstract: Diffusion barrier properties of electrochemically deposited Ni, Co, and Ni-Co alloys were examined in the Ni(Co)/Cu binary system and the Au/Ni/Cu ternary system. Ni and Co were electrodeposited from sulfate or sulfamate (Ni) solutions in the presence of boric acid, at pH 3.30. Electroless Ni and Co deposited either from sulfate or sulfamate solution using sodium hypophosphite or dimethylamine borane as the reducing agent. Eleetroless gold was deposited from cyanide solutions using potassium borohydride as the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(43 citation statements)
references
References 0 publications
0
43
0
Order By: Relevance
“…The penetration depth for Ni and Co into Cu was deeper than the depth for Cu in Ni, Co or Ni 71 Co 29 . Among them, the penetration of Co profile into Cu was the deepest for the Cu/Co stack as shown in Figure 9b.…”
Section: Ecs Journal Of Solid State Science and Technology 5 (2) Q24mentioning
confidence: 76%
See 1 more Smart Citation
“…The penetration depth for Ni and Co into Cu was deeper than the depth for Cu in Ni, Co or Ni 71 Co 29 . Among them, the penetration of Co profile into Cu was the deepest for the Cu/Co stack as shown in Figure 9b.…”
Section: Ecs Journal Of Solid State Science and Technology 5 (2) Q24mentioning
confidence: 76%
“…This pulse scheme was to allow the replenishment of metal ions at the vicinity of substrate surface and to avoid the compositional change as a result of ion depletion. The layer plated with each pulse was identical to the NiCo layer used in the previous study and a composition of Ni 71 Co 29 was obtained by SEM-EDS analysis. To be consistent, the pure Ni was plated with the same pulse scheme.…”
Section: Ecs Journal Of Solid State Science and Technology 5 (2) Q24mentioning
confidence: 99%
“…Synthesis and structures of [1][2][3][4][5][6] Three new cobalt pyrazolate complexes were synthesized using either standard salt elimination routes from cobalt halides and the sodium or lithium salt of 3,5-(CF 3 ) 2 -Pz or by oxidative addition of the N-H bond of the parent pyrazole (3, ) 2 -PzH) to the highly reactive zero-valent Co complex Co(PMe 3 ) 4 (Scheme 1). The use of n-BuLi to generate the pyrazolate lithium salt was the first route explored.…”
Section: Resultsmentioning
confidence: 99%
“…While films of pure metallic cobalt do not make good diffusion barrier layers due to the presence of grain boundaries that allow diffusion of copper, it has been shown that cobalt alloys are promising for use as barrier layers in copper interconnects, especially alloys containing phosphorus. 1 For example, Ekerdt and coworkers recently described the CVD growth of amorphous Co(P) alloys containing 1-5% P from [Co 2 (CO) 8 ] and PMe 3 or from the single source precursor [Co(PMe 3 ) 4 ]. These films been shown to be potential diffusion barrier layers, since they allow virtually no copper diffusion after annealing.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, electroless plating has found many new applications in electronics manufacturing, especially for packaging and for producing diffusion barriers. 211,212 Electroless plating requires a more elaborate bath control than electroplating, but on the other hand, it provides better throwing power and it does not require conducting substrates.…”
Section: Electrochemical Engineering Aspects Of Electrodepositionmentioning
confidence: 99%